What it means to be a "true American": Ethnonationalism and voting in the 2016 U.S. presidential election. Issue 1 (3rd August 2020) - Thompson, Jack
Abstract: A number of important factors predicted white people vote choice in the 2016 U.S. presidential election, including voters' economic assessments, sexist attitudes, racial resentment, and status threat. In this paper, I establish that ethnonationalism—a set of beliefs concerning what it means to be a "true" American—was also a significant factor in the estimations of White Americans when casting their vote for president in 2016. Data from a nationally representative sample of White Americans show that ethnonationalism was a robust predictor of vote choice for Trump even after controlling for predictors known to shape vote choice, including economic assessments, sexist attitudes, racial resentment, status threat, and sociodemographic indicators. These results indicate that ethnonationalism, although correlated with some of these factors, operated primarily as an independent factor that shaped White vote choice. The findings have important implications concerning the electoral activation of White majorities concerned about the perceived threat that demographic change poses to American national identity.